The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1034/j.1399-3011.2003.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR‐derived model of interconverting conformations of an ICAM‐1 inhibitory cyclic nonapeptide

Abstract: We have produced by phage-display a disulfide-linked cyclic nonapeptide (inhibitory peptide-01, IP01), CLLRMRSIC, that binds to intracellular adhesion molecule-1 (ICAM-1) and blocks binding to its counter-structure, leukocyte functional antigen-1 (LFA-1). As a first step towards improving its pharmacologic properties, we have performed a structural and functional analysis of this peptide inhibitor to determine the features relevant to ICAM-1 binding. We report here the solution model of our initial product, IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…For IP01, BRIKARD generated low-energy conformations within 0.83–0.97 Å of all four major conformations identified by NMR 17 in 0.14 wallclock hours. The torsional angles of residue 4 (ARG) are distinct for each NMR state, so we use them to visualize the extent of conformational sampling in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…For IP01, BRIKARD generated low-energy conformations within 0.83–0.97 Å of all four major conformations identified by NMR 17 in 0.14 wallclock hours. The torsional angles of residue 4 (ARG) are distinct for each NMR state, so we use them to visualize the extent of conformational sampling in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Other laboratories [85][86][87][88][89][90] have synthesized interface peptides based on the binding sequence for ICAM-1 derived from the crystal structure of the complex [91]. We have used NMR to determine the solution structure of our peptides [92], and have docked the most active molecules onto the surface of ICAM-1 in a manner which reveals additional details relevant for the understanding of the relationship between peptide structure and activity [93], particularly the importance of amino acid residues enriched at the sites of protein-protein interaction. Other β2 integrin inhibitors are being pursued after the discovery of an LLG interface peptide sequence [94].…”
Section: Resultsmentioning
confidence: 99%
“…The peptides that we identified in this study may serve as lead compounds for further optimization. The optimization of peptide antagonist activity through alanine and homologous amino acid substitution has resulted in 2-to 3-log improvements in inhibitory activity in other systems and may be justified in this system as well (35,37). Finally, structural information about peptides may be used as a guide to create orally available nonpeptide organics.…”
Section: Vol 79 2005 Peptide Inhibitors Of Snv Entry 7323mentioning
confidence: 99%
“…In fact, 10 of 11 peptides (group 4) with the greatest inhibition of SNV infectivity did not have significant sequence relatedness to SNV glycoproteins. Identification of inhibitory peptides that do not have significant sequence relatedness to native ligands has been described in other systems (35)(36)(37), and a large amount of work has indicated that nonhomologous amino acids may mimic the binding activities of each other (reviewed in reference 35). In addition, a comparison of the peptide sequences homologous with SNV to HTNV and PHV glycoproteins did not clearly identify possible contact points of FIG.…”
Section: Vol 79 2005 Peptide Inhibitors Of Snv Entry 7323mentioning
confidence: 99%
See 1 more Smart Citation